1998
DOI: 10.1136/adc.78.4.371
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary CD4+ T lymphocytopenia

Abstract: Two siblings suVering from mental retardation, progressive bronchiectasis, extensive warts, and persistent hepatitis B are described. The propositus also had an unusual physiognomy and non-specific colitis. Both patients had a marked decrease in the population of CD4+ helper T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 5 publications
2
19
1
Order By: Relevance
“…The normal density of CD3 expression of T cells found in our patient may be explained by the peripheral expansion of T cells. Other reports about ICL show a great variability in T cell subsets, ranging from normal to enhanced expression of CD45RO [23, 24, 25]. Depletion of CD4+CD45RA+ cells could be caused by accelerated apoptosis of these cells, but we found that the apoptotic rate of CD4+CD45RA+ cells was not increased compared to healthy controls.…”
Section: Discussioncontrasting
confidence: 49%
“…The normal density of CD3 expression of T cells found in our patient may be explained by the peripheral expansion of T cells. Other reports about ICL show a great variability in T cell subsets, ranging from normal to enhanced expression of CD45RO [23, 24, 25]. Depletion of CD4+CD45RA+ cells could be caused by accelerated apoptosis of these cells, but we found that the apoptotic rate of CD4+CD45RA+ cells was not increased compared to healthy controls.…”
Section: Discussioncontrasting
confidence: 49%
“…Recently, 2 cases of hereditary CD4 ϩ T-cell lymphopenia with normal serum levels were also reported. 81 Interestingly both patients presented with extensive warts. Epidermodysplasia verruciformis (EV) is a heritable syndrome that is also characterized by extensive warts and is often associated with CD4 ϩ T-cell lymphopenia.…”
Section: New Implications Concerning the Key Role Of Ciita Pivmentioning
confidence: 95%
“…Patients with Down syndrome are known to have immunological abnormalities including decreased numbers of CD4+ T-lymphocytes [5], but the extent of CD4+ T-lymphocytopenia is milder than that observed in ICL [1]. Genetic factors may cause ICL [2,6], and the identification of trisomy 21 as a cause of ICL may aid in the identification of these genes. …”
mentioning
confidence: 99%